1982
DOI: 10.2337/diab.31.9.789
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aldose Reductase Inhibition on Motor Nerve Conduction Velocity in Diabetic Rats

Abstract: This study examined the effects of an aldose reductase inhibitor (CP 45634, Sorbinil, Pfizer, New York, New York) on the neuropathy of streptozotocin-induced diabetic rats. Sorbinil treatment for 4 wk reduced sciatic nerve sorbitol concentration and improved motor nerve conduction velocity in diabetes of 2-9 mo duration. It remains to be determined whether Sorbinil can prevent chronic diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Another study, which used methods essentially similar to ours, revealed an even more marked reduction in sciatictibial conduction velocity than that described here. 6 We are unable to shed further light on these disagreements, but it is perhaps pertinent to stress the importance of nerve temperature measurement as part of the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Another study, which used methods essentially similar to ours, revealed an even more marked reduction in sciatictibial conduction velocity than that described here. 6 We are unable to shed further light on these disagreements, but it is perhaps pertinent to stress the importance of nerve temperature measurement as part of the procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Aldose reductase inhibitors have been found to prevent and, in some cases, reverse abnormalities in sciatic nerve Na + -K + -ATPase activity, axonal transport, and nerve conduction velocity in experimental diabetes (27)(28)(29)(30). Although most of these studies have concentrated on somatic myelinated nerves, a few studies have suggested that there is an effect on biochemical (45), pathophysiological, and structural histopathology (14) involving the autonomic nervous system as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established the participation of the sorbitol and myo-inositol pathways in the development of some of the complications of experimental diabetes (27)(28)(29)(30). Aldose reductase inhibitors have been found to prevent and, in some cases, reverse abnormalities in sciatic nerve Na + -K + -ATPase activity, axonal transport, and nerve conduction velocity in experimental diabetes (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies, aldose reductase inhibitors (ARI) prevented development of nerve conduction or ultrastructural abnormalities associated with experimental diabetes [122,123,124]. In a one-year clinical trial, a high dose of the ARI, tolrestat, was associated with improved nerve conduction velocities (NCV), but not painful neuropathic symptoms [125].…”
Section: Investigational Therapiesmentioning
confidence: 99%